Studi Pengaruh Konstanta Spring CVT terhadap Daya dan Torsi pada Motor Bensin Kapasitas Silinder 110 CC (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This study aims to analyze the effect of variations in the Continuously Variable Transmission (CVT) spring constant and the type of fuel on the performance of a 110 CC gasoline motorcycle engine. The CVT system is one of the important components in an automatic motorcycle that functions to transmit power from the engine to the rear wheels efficiently. CVT performance is greatly influenced by the spring constant used, because this component is directly related to the automatic gear ratio shifting process. On the other hand, the type of fuel also has an important role because it is related to the quality of combustion and the efficiency of energy produced by the engine. The test results show that the use of a CVT spring with a constant of 18.05 N/cm combined with Pertamax fuel is able to provide the best engine performance. In this configuration, the engine reaches a maximum power of 7.84 HP at 8200 rpm and a maximum torque of 9.30 Nm at 6200 rpm. This combination is proven to be the most optimal in increasing power and torque, thus providing more responsive acceleration. Furthermore, the use of a CVT spring with a constant of 25.20 N/cm combined with Pertamax also shows quite good performance, namely with a maximum power of 7.38 HP and a maximum torque of 8.56 Nm. Although the results are not as high as the first configuration, this combination is still quite effective in improving engine performance. Meanwhile, when using a spring with a higher constant of 33.69 N/cm, the resulting power tends to decrease to 7.02 HP with a torque of 8.02 Nm. In addition, the initial acceleration in this configuration is less responsive so it is not recommended for optimal performance.